Composite regulation and control method for improving performance of laser additive manufacturing high-strength aluminum alloy
By uniformly mixing micro-scale ceramic particles with AlMgScZr alloy powder in laser additive manufacturing, and combining heat treatment technology, the problems of ceramic particles agglomeration and thermal stress are solved, significantly improving the mechanical properties of high-strength aluminum alloys and reducing the preparation cost.
Patent Information
- Application Number
- CN202411514933.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-25
AI Technical Summary
While improving mechanical properties, existing laser additive-made aluminum alloy materials face problems of ceramic particles agglomeration and thermal stress, resulting in limited performance improvement or high production costs.
By uniformly mixing micron-scale ceramic particles with AlMgScZr alloy powder in a specific proportion, and combining heat treatment technology, laser additive manufacturing and heat treatment process parameters are optimized to accurately regulate the microstructure of the composite material.
The uniform dispersion of ceramic particles in the laser melt pool is achieved, the solidification structure is optimized, the tensile strength, yield strength and elongation of the material are significantly improved, and the preparation cost is reduced.
Smart Images

Figure CN119501091A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of laser additive manufacturing of high-strength aluminum alloy materials, and relates to a composite control method for improving the performance of laser additive manufacturing of high-strength aluminum alloys. Background Art
[0002] As the preferred material for achieving lightweight structures, aluminum alloys have shown great application potential in many fields such as aerospace, transportation, and shipbuilding. In order to meet the needs of the aviation field for additive manufacturing (i.e. 3D printing) of aluminum alloy parts, AIRBUS APWORKS, a well-known foreign Airbus subsidiary, innovatively launched Scalmalloy in 2006 - an Al-Mg-Sc aluminum alloy powder material designed specifically for additive manufacturing. Scalmalloy is not only the world's first aluminum alloy material developed specifically for 3D printing, but also has unique solidification characteristics and processes through carefully designed composition ratios. In the laser micro-melting pool, the alloy mainly precipitates Al3Sc or Al3(Sc 1-x ; Zr x ) particle phase, which not only acts as a nucleation core and effectively refines the grains, but also plays a role in inhibiting grain growth. With its excellent room temperature tensile strength of more than 500MPa, reaching the international top level, Scalmalloy has been successfully used in the 3D printing manufacturing of A320 aircraft cabin structural parts. Related studies have shown that the addition of the alloying element scandium (Sc) has a significant effect on the microstructure and properties of aluminum alloys. It is not only an effective refiner of the cast grain structure of aluminum alloys, a strong inhibitor of recrystallization, but also an excellent hardener. At the same time, the addition of zirconium (Zr) can further enhance and stabilize these effects of scandium (Sc). However, it is extremely difficult to dissolve more than 1.2wt% of scandium (Sc) in the aluminum lattice, which requires rapid cooling during the solidification process; in addition, the cost of scandium (Sc) is relatively high, and it is not suitable to add a large amount from the perspective of the economy of material production and application.
[0003] In order to improve the comprehensive performance of high-strength aluminum alloys, researchers have prepared aluminum-based composites by introducing a variety of reinforcements. While retaining the original properties of the alloy matrix, aluminum-based composites also exhibit superior properties such as higher specific strength, specific stiffness, and excellent wear resistance. Among them, adding ceramic particles to aluminum alloys has been proven to be an extremely effective strategy that can not only optimize the solidification structure but also significantly enhance the toughness of the material. This method has been applied in the field of laser additive manufacturing. At present, the research on laser additive manufacturing of aluminum-based composites focuses on the addition of nanoparticle reinforcement phases. The addition of nano-ceramic particles can not only improve the absorption efficiency of aluminum alloys for lasers, but also act as heterogeneous nucleation points to effectively refine the grain size, thereby further optimizing the solidification structure. However, there are strong van der Waals forces between nanoparticles, which makes them very easy to agglomerate, which limits the effective content of the reinforcement phase in the composite material, usually less than 2wt%, thereby limiting its improvement in alloy performance. Summary of the invention
[0004] The purpose of the present invention is to propose an innovative composite control method, which improves the performance of laser additive manufacturing of high-strength aluminum alloys by combining the addition of micron-sized ceramic particles with heat treatment technology. The high-strength aluminum alloy prepared by this method not only exhibits excellent forming performance during the manufacturing process, but also has excellent mechanical properties, which can meet the needs of high-strength and high-performance materials in multiple fields such as aerospace, transportation, and shipbuilding.
[0005] To achieve the above objectives, the present invention adopts the following technical solutions for implementation:
[0006] A composite control method for improving the performance of high-strength aluminum alloy manufactured by laser additive manufacturing, comprising the following steps:
[0007] Step 1: Using a mechanical mixer, the micron ceramic particles and the micron AlMgScZr alloy powder are uniformly mixed in different mass proportions to prepare a particle-reinforced aluminum-based composite powder material suitable for laser additive manufacturing;
[0008] Step 2: Build a 3D geometric model of the target part, perform slicing and process planning on it, and provide a basis for subsequent laser forming operations;
[0009] Step 3: Based on the slice data obtained in step 2, the aluminum-based composite powder obtained in step 1 is subjected to layer-by-layer laser selective melting and consolidation using laser additive manufacturing technology to obtain a ceramic particle-reinforced aluminum-based composite part;
[0010] Step 4: heat-treating the ceramic particle reinforced aluminum-based composite material parts obtained in step 3 to finally obtain high-strength aluminum alloy material parts with high strength and high elongation.
[0011] Furthermore, the average particle size of the micron AlMgScZr alloy powder in step 1 is 10 to 65 μm, and the composition of the alloy powder, calculated by mass percentage, includes 2.0 to 6.0% magnesium (Mg) element, 0.5 to 1.2% scandium (Sc) element, 0.3 to 0.9% zirconium (Zr) element, and the rest is aluminum (Al) element and trace impurities introduced during manufacturing.
[0012] Furthermore, the average size of the micron ceramic particles in step 1 is 5 to 40 μm, and the mass proportion in the mixed composite material is 5 to 20%. The aspect ratio of the ceramic particles is 2.0, and the ceramic particles can be selected from materials such as SiC, TiB2, TiN, B4C, and ZrO2.
[0013] Furthermore, the mechanical mixing equipment in step 1 is a V-shaped mixer equipped with a stainless steel mixing tank and mixing balls, the diameter of the mixing balls is 6 to 8 mm, and the ball-to-material mass ratio is 1:1.2. The speed of the mixer is 40 to 60 rpm, and the duration is 5 to 9 hours.
[0014] Furthermore, the three-dimensional geometric model of the part in step 2 is constructed by three-dimensional modeling software, and the slicing processing and process planning are to convert the model into an STL file format, import it into the slicing software for slicing, and import the final file into the laser additive manufacturing equipment to prepare for selective laser melting.
[0015] Furthermore, the laser additive manufacturing forming process in step 3 is as follows: using the selective laser melting technology, the composite powder pre-mixed evenly in step 1 is placed in a powder bin, argon gas is introduced into the equipment to keep the oxygen content below 100 ppm, and according to the layered slicing data in step 2, a powder scraper evenly spreads a layer of powder on a 6061Al substrate preheated to 90±10°C, and then the laser selectively melts the powder according to a predetermined scanning path, and gradually deposits the target part through layer-by-layer melting. The process parameters are: laser power 240~500W, scanning speed 600~2400mm / s, scanning spacing 120~160μm, powder layer thickness 15~85μm, interlayer rotation angle 67~90°, and partitioned strip scanning strategy.
[0016] Further, the obtained ceramic particle reinforced aluminum-based composite material parts are heat treated in a resistance heat treatment furnace at a temperature of 200 to 380° C. for a holding time of 0.5 to 5 hours, followed by air cooling.
[0017] The above technical solution of the present invention has the following beneficial technical effects:
[0018] 1. Challenges and solutions in ceramic particle agglomeration and laser additive manufacturing
[0019] In the aluminum alloy matrix, nanoparticles are prone to agglomeration due to strong van der Waals forces, while micron-sized particles, although their van der Waals forces are weakened, still face the challenge of uniform dispersion. Ensuring that micron-sized ceramic particles are evenly dispersed in aluminum alloy powders and preventing agglomeration are the key to improving the uniformity of the internal structure and performance stability of composite materials. At the same time, the thermal stress caused by rapid cooling during laser additive manufacturing can easily cause the material to crack. To solve these problems, it is necessary to precisely control the laser parameters and optimize the heat treatment process. In addition, the cost of the Sc element is high and the amount added is limited. How to improve the performance of aluminum alloys without increasing the Sc content is a cost-effective problem.
[0020] 2. Innovation and unique solutions
[0021] The present invention uniformly mixes micron-sized ceramic particles with AlMgScZr alloy powder in a specific ratio, thereby achieving small segregation and uniform dispersion of ceramic particles in the laser molten pool, optimizing the solidification structure, and improving the mechanical properties. At the same time, by optimizing the laser additive manufacturing and heat treatment process parameters, the microstructure of the composite material is precisely controlled, thermal stress is effectively alleviated, crack formation is avoided, and the tensile strength, yield strength and elongation of the material are significantly improved. In addition, by optimizing the alloy composition and adding more cost-effective ceramic particles, the preparation cost is reduced and the excellent mechanical properties are maintained, providing new possibilities for the application of high-strength aluminum alloys in aerospace and other fields.
[0022] 3. Reasons why this invention is superior to other patents
[0023] The present invention proposes an innovative composite control method to solve the problems of agglomeration and thermal stress by deeply studying the interaction mechanism between ceramic particles and alloy powders and the thermal stress control mechanism in laser additive manufacturing. It combines advanced material design, laser additive manufacturing process and heat treatment process to form a complete technical system. The final room temperature tensile strength of the parts exceeds 540MPa, the yield strength exceeds 490MPa, and the elongation exceeds 10%, which is better than other patents. Other patents fail to solve the problem of ceramic particle agglomeration, or have deficiencies in alloy composition design, powder mixing technology, laser process parameters and heat treatment technology optimization, resulting in limited performance improvement or high preparation costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a macroscopic image of a sample block of the ceramic particle reinforced aluminum matrix composite material prepared in Example 1;
[0025] Figure 2 An optical micrograph of a deposition cross section of a ceramic particle reinforced aluminum matrix composite material sample prepared in Example 1;
[0026] Figure 3The stress-strain curves of the room temperature tensile test of the ceramic particle reinforced aluminum-based composite material samples prepared in Example 1, Example 2, and Example 3 are shown. DETAILED DESCRIPTION
[0027] The technical solutions in the embodiments of the present application will be described in detail and comprehensively below in combination with the embodiments of the present application and the drawings therein. It should be clear that the embodiments shown are only some examples of the present application, not all. Based on these embodiments, all other embodiments that can be derived by ordinary technicians in this field without creative work are deemed to fall within the protection scope of the present application.
[0028] Example 1
[0029] A composite control method for improving the performance of high-strength aluminum alloy manufactured by laser additive manufacturing, the specific steps are as follows:
[0030] (1) The average particle size of the AlMgScZr alloy powder is 15 microns, and the specific ratio of its alloy elements is: Mg element content 5.0wt%, Sc element content 0.9wt%, Zr element content 0.6wt%, and the rest is Al element. SiC particles accounting for 8% of the total mass of the mixed composite powder are introduced into the alloy powder, the average size of the SiC particles is 5μm, and the aspect ratio of the SiC particles is 2.0. The mixing process is completed in a V-type mechanical mixer, mixing at a speed of 46rpm for 7h, so that the SiC particles and the AlMgScZr alloy powder are evenly mixed to form a SiC / AlMgScZr composite powder. During this process, the ball-to-material mass ratio is set to 1:1.2 to ensure the mixing effect.
[0031] (2) A rectangular model and a tensile part model with a size of 76 mm × 15 mm × 15 mm were constructed using 3D UG software on a computer. The model was converted into an STL file and imported into a slicing software for slicing. The data was imported into a selective laser melting device for subsequent printing and processing.
[0032] (3) Selective laser melting technology was used to prepare micron SiC particle reinforced AlMgScZr composite powder material. The model of the selective laser melting equipment was EP M250. 6061Al was selected as the substrate material and the substrate was preheated to 100°C before forming. At the same time, argon gas was introduced into the equipment to ensure that the oxygen content was less than 100ppm, providing an oxygen-free environment for the forming of the material. The powder layer thickness was set to 30μm, the laser power was 300W, the scanning speed was 1000mm / s, the scanning spacing was 130μm, the interlayer rotation angle was 70°, and the partitioned strip scanning strategy was adopted.
[0033] (4) The ceramic particle reinforced aluminum matrix composite material prepared by the process of the above embodiment has a density of up to 99.89%, excellent forming quality, and no defects such as pores and cracks. The macroscopic photo of the formed sample is shown in Figure 1 As shown, it shows the good overall performance of the material. At the same time, the metallographic photo ( Figure 2 ) further reveals the distribution of micron SiC particles in the molten pool.
[0034] (5) The obtained ceramic particle reinforced aluminum matrix composite parts are heat treated by first heating the resistance heat treatment furnace to 280°C, then placing the parts in the heat treatment furnace, taking them out after a 3-hour heat preservation time, and cooling them at room temperature. After heat treatment, the room temperature tensile strength of the material is 551 MPa, the yield strength is 506 MPa, and the elongation at break is 11.6%. Its stress-strain curve is shown in Figure 3 As shown, it exhibits excellent mechanical properties.
[0035] Example 2
[0036] A composite control method for improving the performance of high-strength aluminum alloy manufactured by laser additive manufacturing, the specific steps are as follows:
[0037] (1) The average particle size of the AlMgScZr alloy powder is 35 microns, and the specific ratio of its alloy elements is: Mg element content 5.0wt%, Sc element content 0.9wt%, Zr element content 0.6wt%, and the rest is Al element. B4C particles accounting for 10% of the total mass of the mixed composite powder are introduced into the alloy powder. The average size of the B4C particles is 15μm, and the aspect ratio of the B4C particles is 2.0. The mixing process is completed in a V-type mechanical mixer, and the mixing speed is 53rpm for 8h to make the B4C particles and the AlMgScZr alloy powder evenly mixed to form a B4C / AlMgScZr composite powder. In this process, the ball-to-material mass ratio is set to 1:1.2 to ensure the mixing effect.
[0038] (2) A rectangular model and a tensile part model with a size of 76 mm × 15 mm × 15 mm were constructed using 3D UG software on a computer. The model was converted into an STL file and imported into a slicing software for slicing. The data was imported into a selective laser melting device for subsequent printing and processing.
[0039] (3) Micron B4C particle reinforced AlMgScZr composite powder material was prepared by selective laser melting technology. The model of the selective laser melting equipment was EP M250. 6061Al was selected as the substrate material and the substrate was preheated to 100°C before forming. At the same time, argon gas was introduced into the equipment to ensure that the oxygen content was less than 100ppm, providing an oxygen-free environment for the forming of the material. The powder layer thickness was set to 40μm, the laser power was 330W, the scanning speed was 1500mm / s, the scanning spacing was 140μm, the interlayer rotation angle was 80°, and the partitioned strip scanning strategy was adopted.
[0040] (4) The ceramic particle reinforced aluminum matrix composite material prepared by the process of the above embodiment has a density of up to 99.91%, excellent forming quality, and no defects such as pores and cracks.
[0041] (5) The obtained ceramic particle reinforced aluminum matrix composite parts are heat treated by first heating the resistance heat treatment furnace to 340°C, then placing the parts in the heat treatment furnace, taking them out after a holding time of 1.5 hours, and cooling them at room temperature. After heat treatment, the room temperature tensile strength of the material is 556MPa, the yield strength is 510MPa, and the elongation at break is 10.5%. Its stress-strain curve is shown in Figure 3 As shown, it exhibits excellent mechanical properties.
[0042] Example 3
[0043] A composite control method for improving the performance of high-strength aluminum alloy manufactured by laser additive manufacturing, the specific steps are as follows:
[0044] (1) The average particle size of the AlMgScZr alloy powder is 45 microns, and the specific ratio of its alloy elements is: Mg element content 5.0wt%, Sc element content 0.9wt%, Zr element content 0.6wt%, and the rest is Al element. ZrO2 particles accounting for 15% of the total mass of the mixed composite powder are introduced into the alloy powder, the average size of the ZrO2 particles is 20μm, and the aspect ratio of the ZrO2 particles is 2.0. The mixing process is completed in a V-type mechanical mixer, and the mixing speed is 55rpm for 8h to uniformly mix the ZrO2 particles and the AlMgScZr alloy powder to form a ZrO2 / AlMgScZr composite powder. In this process, the ball-to-material mass ratio is set to 1:1.2 to ensure the mixing effect.
[0045] (2) A rectangular model and a tensile part model with a size of 76 mm × 15 mm × 15 mm were constructed using 3D UG software on a computer. The model was converted into an STL file and imported into a slicing software for slicing. The data was imported into a selective laser melting device for subsequent printing and processing.
[0046] (3) Selective laser melting technology was used to prepare micron ZrO2 particle reinforced AlMgScZr composite powder material. The model of the selective laser melting equipment was EP M250. 6061Al was selected as the substrate material and the substrate was preheated to 100°C before forming. At the same time, argon gas was introduced into the equipment to ensure that the oxygen content was less than 100ppm, providing an oxygen-free environment for the forming of the material. The powder layer thickness was set to 50μm, the laser power was 420W, the scanning speed was 1800mm / s, the scanning spacing was 150μm, the interlayer rotation angle was 90°, and the partitioned strip scanning strategy was adopted.
[0047] (4) The ceramic particle reinforced aluminum matrix composite material prepared by the process of the above embodiment has a density of up to 99.87%, excellent forming quality, and no defects such as pores and cracks.
[0048] (5) The obtained ceramic particle reinforced aluminum matrix composite parts are heat treated by first heating the resistance heat treatment furnace to 400°C, then placing the parts in the heat treatment furnace, taking them out after a holding time of 0.5 h, and cooling them at room temperature. After heat treatment, the room temperature tensile strength of the material is 561 MPa, the yield strength is 513 MPa, and the elongation at break is 12.4%. Its stress-strain curve is shown in Figure 3 As shown, it exhibits excellent mechanical properties.
Claims
1. A composite control method for improving the performance of high-strength aluminum alloy manufactured by laser additive manufacturing, characterized in that: The following steps are involved: The micron-sized ceramic particles and the micron-sized AlMgScZr alloy powder are uniformly mixed by mechanical mixing in different mass proportions; wherein the particle size of the micron-sized AlMgScZr alloy powder is 10 to 65 μm, and the composition of the AlMgScZr alloy powder is calculated by mass percentage, including 2.0 to 6.0% magnesium, 0.5 to 1.2% scandium, 0.3 to 0.9% zirconium, and the rest is aluminum; ceramic particles are introduced into the above AlMgScZr alloy powder, the average size of the ceramic particles is 5 to 40 μm, the mass proportion of the ceramic particles in the mixed composite powder is 5% to 20%, and the ceramic particles are selected from SiC, TiB2, TiN, B4C or ZrO2; The selected laser melting process parameters adopted are: preheating of the forming substrate at 90±10℃, laser power of 240~500W, scanning speed of 600~2400mm / s, scanning spacing of 120~160μm, powder layer thickness of 15~85μm, and interlayer rotation angle of 67~90°; the obtained ceramic particle reinforced aluminum-based composite parts are heat treated at a temperature of 200~380℃, a holding time of 0.5~5h, and air cooling after holding.
Citation Information
Cited By
High-modulus and high-strength aluminum-based composite material and preparation method thereof
CN120443011A
Lightweight vehicle body structure integrated manufacturing process based on additive manufacturing
CN120920740A
TiC ceramic particle regulated and controlled 2xxx series aluminum alloy composite material and preparation method thereof
CN121017565A